2013
DOI: 10.7589/2012-06-172
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibodies to Borrelia Burgdorferi, Anaplasma Phagocytophilum, and Babesia Microti in Recaptured White-Footed Mice

Abstract: A mark-release-recapture study was conducted during 2007 through 2010 in six, tick-infested sites in Connecticut, United States to measure changes in antibody titers for Borrelia burgdorferi sensu stricto, Anaplasma phagocytophilum, and Babesia microti in Peromyscus leucopus (white-footed mice). There was an overall recapture rate of 40%, but only four tagged mice were caught in ≥2 yr. Sera from 561 mice were analyzed for total antibodies to B. burgdorferi and A. phagocytophilum by using whole-cell or recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…6B), as we have done previously [43]. The reciprocal titer levels were comparable to measured levels against whole Borrelia lysates in infected wild animals [77], [78]. Further studies are needed to determine the immunogenicity of BB0347 in humans, as well as the prevalence and distribution of αBB0347 antibodies in an infected population of patients and the protective efficiency of the antibodies.…”
Section: Discussionsupporting
confidence: 74%
“…6B), as we have done previously [43]. The reciprocal titer levels were comparable to measured levels against whole Borrelia lysates in infected wild animals [77], [78]. Further studies are needed to determine the immunogenicity of BB0347 in humans, as well as the prevalence and distribution of αBB0347 antibodies in an infected population of patients and the protective efficiency of the antibodies.…”
Section: Discussionsupporting
confidence: 74%
“…These pathogens can serve as a useful model for the study of coinfection because they are commonly found together in reservoir hosts, ticks and humans. These reservoir hosts often are infected with Borrelia burgdorferi sensu lato , and therefore constitute an ‘infected niche’ that is encountered by any of the other Ixodes -transmitted pathogens [6, 7]. We review the pathogen combinations found in Ixodes ticks and reservoir hosts around the world, but focus on coinfection with B. burgdorferi sensu stricto and Babesia microti , the major etiologic agents of Lyme disease and human babesiosis in the United States, respectively [8, 9].…”
Section: Ixodes-borne Pathogens As a Model System To Study Vector-bormentioning
confidence: 99%
“…B. burgdorferi is highly prevalent among reservoir hosts in endemic areas [7]. As B. microti infected nymphs disperse into B. burgdorferi endemic areas that are B. microti free, they most likely inoculate B. microti into reservoir hosts that are infected with B. burgdorferi.…”
Section: Coinfection Increases the Suitability Of P Leucopus As Resementioning
confidence: 99%
“…in cerebrospinal fluid (CSF), synovial fluid, skin bioptates and urine samples [18][19][20]. Taking into account that the etiologic agent of LD, Borrelia burgdorferi sensu lato, was recovered first from the tick Ixodes dammini in the year 1982 [2] and then from a skin biopsy, CSF and blood specimens of patients with LB around the world [2,[21][22][23][24][25], the main aim of this study was to discuss the utility of introduction of a well-optimized, sensitive and highly specific quantitative real-time PCR assay into the diagnostics of Borrelia burgdorferi sensu lato infections.…”
mentioning
confidence: 99%